Microbial Omens: The Predictive Power of Microbiome Signatures in Cancer Risk - Fakruddin, M.; Oyshe, I.I.; Islam, S.M.B.U.; Safa, A.; Sultana, J.; Bulbul, N.; Shishir, Md.A.; Факруддін, М.; Ойше, І.І.; Іслам, С.М.Б.У.; Сафа, А.; Султана, Д.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
The human microbiome, a complex ecosystem of microorganisms inhabiting various niches within the body, has emerged as a potential harbinger of health and disease. In recent years, a growing body of research has illuminated the intricate interplay between the microbiome and cancer risk. This review article explores the burgeoning field of microbiome signatures as predictive tools for assessing the risk of cancer development. The microbiome's role in maintaining homeostasis, modulating immune responses, and influencing metabolic pathways has provided a fertile ground for investigating its association with carcinogenesis. With a focus on distinct microbial compositions and specific molecular markers, we delve into the intricate mechanisms underlying the potential of microbiome signatures to forecast cancer risk. From gastrointestinal to genitourinary malignancies, we survey the landscape of microbiome-related studies that have unveiled promising associations between microbial dysbiosis and the initiation of carcinogenesis. Furthermore, we discuss the integration of cutting-edge technologies, including high-throughput sequencing and advanced bioinformatics, in deciphering complex microbiome data and deriving predictive models. The challenges of standardization, validation, and clinical translation of microbiome-based risk assessments are also addressed. As microbiome research evolves, it offers unprecedented insights into the early stages of cancer development, heralding a paradigm shift in personalized cancer risk assessment. By presenting an overview of current achievements, limitations, and prospects, this review elucidates the transformative potential of microbial omens in shaping the landscape of cancer prediction and preventive strategies.